Nature as a postcolonial mirror: Memory and identity in Salman Rushdie’s Midnight’s Children - Md. Jobaar Talukder; A. H. M. Aktarul Islam (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2025)
This qualitative study examines the intersection of ecocriticism and postcolonialism in Salman Rushdie’s novel Midnight’s Children, highlighting how these frameworks illuminate the emotional and psychological dimensions of his characters. Rushdie is a renowned writer who gained fame around the time British rule in South Asia was coming to an end. He is known for telling complex stories and exploring the inner thoughts of both male and female characters. His characters often struggle to find their identity in a society that marginalizes them. Many of his stories show feelings of loneliness, unfulfilled love, disappointment, betrayal, and failed dreams. Even when his characters are honest and loyal, they are often left out or ignored. By focusing on human emotion, nature, and culture, Rushdie highlights essential aspects of the human experience. He also shows how people feel and think during times of crisis, such as war. In these moments, emotions play a crucial role in helping people heal and rebuild themselves. This research examines how Rushdie integrates nature and postcolonial themes in his writing to enhance our understanding of both personal and collective struggles.